Strategies for Bacteriophage T5 Mutagenesis: Expanding the Toolbox for Phage Genome Engineering - Ramirez-Chamorro, Luis; Boulanger, Pascale; Rossier, Ombeline (Frontiers in Microbiology, 2021)
Phage genome editing is crucial to uncover the molecular mechanisms of virus infection and to engineer bacteriophages with enhanced antibacterial properties. Phage genetic engineering relies mostly on homologous recombination (HR) assisted by the targeted elimination of wild-type phages by CRISPR-Cas nucleases. These strategies are often less effective in virulent bacteriophages with large genomes. T5 is a virulent phage that infects Escherichia coli. We found that CRISPR-Cas9 system (type II-A) had ununiform efficacies against T5, which impairs a reliable use of CRISPR-Cas-assisted counterselection in the gene editing of T5. Here, we present alternative strategies for the construction of mutants in T5. Bacterial retroelements (retrons) proved to be efficient for T5 gene editing by introducing point mutations in the essential gene A1. We set up a protocol based on dilution-amplification-screening (DAS) of phage pools for mutant enrichment that was used to introduce a conditional mutation in another essential gene (A2), insert a new gene (lacZα), and construct a translational fusion of a late phage gene with a fluorescent protein coding gene (pb10-mCherry). The method should be applicable to other virulent phages that are naturally resistant to CRISPR/Cas nucleases.